MINI-REVIEW OF NUCLEAR-FACTOR-KAPPA-B IN SILICO STUDIES: Received: 23rd August 2024 Revised: 1st September 2024, 8th September 2024 Accepted: 26th August 2024 - D.A Salam, Dayang-Sharyati; San, Hwang Siaw; Wezen, Xavier Chee (LIFE: International Journal of Health and Life-Sciences, 2024)
This mini-review provides a concise overview of the advancements in computer-assisted methodologies and research related to nuclear factor kappa B (NF-kB) over the past decade. Applying computer-aided or in silico methods to investigating the NF-kB complex offers intriguing options for identifying treatment targets for various disorders involving the NF-kB protein. Compared to traditional in vivo and in vitro investigations, in silico research has multiple advantages, including improved precision, increased efficiency, and eliminating the requirement for human and animal participants. This method creates a framework for evaluating the efficacy of potential treatments against specific molecular targets, allowing for the prediction of their efficacy based on the structural properties of compounds before synthesis for subsequent in vitro and in vivo testing. Targeting the NF-kB protein is critical because it plays a role in many disorders involving immunological and inflammatory responses, stress responses, cellular proliferation, and apoptosis. These findings are essential for guiding future research into the role of the NF-kB protein in human disorders and identifying possible therapeutic targets. This mini-review provides a concise overview of the advancements in computer-assisted methodologies and research related to nuclear factor kappa B (NF-kB) over the past decade. Applying computer-aided or in silico methods to investigating the NF-kB complex offers intriguing options for identifying treatment targets for various disorders involving the NF-kB protein. Compared to traditional in vivo and in vitro investigations, in silico research has multiple advantages, including improved precision, increased efficiency, and eliminating the requirement for human and animal participants. This method creates a framework for evaluating the efficacy of potential treatments against specific molecular targets, allowing for the prediction of their efficacy based on the structural properties of compounds before synthesis for subsequent in vitro and in vivo testing. Targeting the NF-kB protein is critical because it plays a role in many disorders involving immunological and inflammatory responses, stress responses, cellular proliferation, and apoptosis. These findings are essential for guiding future research into the role of the NF-kB protein in human disorders and identifying possible therapeutic targets.